Teknologi Augmented Reality Simulasi Fotolistrik 3D - Afif Rahman Riyanda; Nizwardi Jalinus; Sukardi Sukardi; Waskito Waskito; Fadhli Ranuharja; Agariadne Dwinggo Samala; Novi Hendri Adi; Ika Parma Dewi (Jurnal Teknologi Informasi dan Pendidikan, 2021)
The research has been conducted on the development of the 3D Photoelectric Simulation based on Augmented Reality. This Preliminary study is to analyze the availability of used photoelectric visulations and prakticum in High Schools in Lampung and how many physics teachers have not used teaching aids in the form of photoelctric tools or mercury light source enclosure. Based on the preliminary research, it was concluded that there are still very few physics teachers who use the photoelctric tools or mercury light source enclosure in High School physics learning. Therefore, it is very necessary to develop the Polariskop KIT along with teaching materials with LMS Assistance. The stages of developing the KIT in this preliminary study have only reached the 3D Simulation photoelectric design stage and design validation test.